Eosinophilic Myocarditis as a Cause of Death: A Case Diagnosed at Autopsy. (28th October 2020) - Khokhar, H; Beversdorf, W; Fox, S
Abstract: Introduction/Objective: Eosinophilic (Loffler) myocarditis is a rare disease defined by the influx of eosinophils into the endocardium and myocardium. Etiologies are numerous and include drug or hypersensitivity reactions, hypereosinophilic syndrome, hematologic malignancies, and parasitic infections. It is a diagnostically challenging entity. Presenting symptoms recorded in the literature are indefinite and nonspecific; heart failure, demonstrable arrhythmia, and elevated cardiac biomarkers. This is especially the case among younger, otherwise healthy patients without classical risk factors for atherosclerotic coronary artery disease. Methods: Herein we present several cases of sudden cardiac death in young adults, including a case of unknown eosinophilic myocarditis, which highlights the potential trials in the diagnosis of this disease. Results: Autopsies were performed on several adults (age range, 30-40 years) thought to have died of cardiac causes. This included a 30-year-old African American female with no significant known medical history who presented with a chief complaint of palpitations. The initial clinical impression at an outside institution was of cardiac amyloidosis. But the Technetium99 scan was inconclusive. Despite clinical management, she developed ventricular arrhythmias and could not be resuscitated. There was a vague history of taking nutritional supplements from a local grocery store. Gross findings at autopsy included circumferential subepicardial erythema, thymic enlargement (60g), and congested lungs. The heart was thoroughly sampled. Microscopic examination revealed diffuse infiltration of eosinophils, mast cells, lymphocytes and macrophages with mild myocyte necrosis and interstitial edema in all sections. There were no giant cells, no interstitial deposition of amorphous acellular material and no focus of infarcted myocardium. Thymic sections were histologically normal. Acetylcholine receptor antibody panel was negative. Conclusion: We conclude that eosinophilic myocarditis though rare (0.5% unsuspected and 0.1% suspected cases), is a distinctive cause of death with a specific microscopic presentation. Our case also included thymic enlargement at autopsy – a finding not previously noted.